Impact of dementia on post-hip fracture walking ability: a stratified analysis based on pre-fracture mobility in Swedish cohorts of older adults - Philip D. G. Burenstam Linder; Dorota D. Religa; Fredrik Gustavsson; Maria Eriksdotter; Margareta Hedström; Sara Hägg (BMC Geriatrics)
Abstract Background Hip fractures are a major health concern for older adults, often leading to reduced walking ability. Individuals with dementia may experience worse recovery outcomes. This study aims to explore whether dementia is associated with greater declines in walking ability following hip fractures. Methods This register study used data from the Swedish Hip Fracture Register, including data on four-months follow-up on walking ability. The register data was linked to information on dementia diagnosis from other national registers prior to the fracture. All patients > 60 years who suffered a hip fracture in Sweden between 2010 and 2018 were included. Binary logistic regression was used to analyze the loss of walking ability after the hip fracture with adjustment for confounding factors. Stratified analyses were done in four groups based on pre-fracture walking ability: Alone outdoors, Assisted outdoors, Alone indoors, and Assisted indoors. Results The analysis included 59,402 patients with a hip fracture, of which 17% had dementia prior to the fracture. Having dementia was associated with a complete loss of walking ability four months after hip fracture; the multivariable-adjusted odds ratio for complete loss of walking ability in the dementia group, using the non-dementia group as a reference, was 1.60 (95% Confidence Interval [CI] 1.49–1.72. In analyses stratified by pre-fracture walking ability, the odds ratios were 2.34 (95% Confidence Interval [CI] 2.03–2.69) for Alone outdoors, 1.53 (95% CI 1.29–1.81) for Assisted outdoors, 1.41 (95% CI 1.27–1.56) for Alone indoors, and 1.29 (95% CI 1.09–1.51) for Assisted indoors. Conclusions This study demonstrates that patients with dementia have a greater risk of complete loss of walking ability. The most notable difference was observed in patients who had high walking ability prior to the fracture. These findings suggest the need for tailored rehabilitation programs and enhanced post-operative care protocols for patients with dementia undergoing hip fracture surgery, particularly for those who had high walking ability before the fracture.